11β-Prostaglandin F2α, a bioactive metabolite catalyzed by AKR1C3, stimulates prostaglandin F receptor and induces slug expression in breast cancer. (15th September 2015) - Yoda, Tomomi; Kikuchi, Kyoko; Miki, Yasuhiro; Onodera, Yoshiaki; Hata, Shuko; Takagi, Kiyoshi; Nakamura, Yasuhiro; Hirakawa, Hisashi; Ishida, Takanori; Suzuki, Takashi; Ohuchi, Noriaki; Sasano, Hironobu; et al.
Abstract: Prostaglandins are a group of lipid compounds involved in inflammation and cancer. We focused on PGF2α and its stereoisomer 11β-PGF2α and examined the expression and functions of their cognate receptor (FP receptor) and metabolizing enzymes (AKR1B1 and AKR1C3 respectively) in breast cancer. In immunohistochemical analysis FP receptor status associated with adverse clinical outcome only in the AKR1C3 positive cases. Therefore, we studied FP receptor-mediated functions of 11β-PGF2α using FP receptor expressed MCF-7 cell line (MCF-FP). 11β-PGF2α treatment phosphorylated ERK and CREB and induced Slug expression through FP receptor in MCF-FP, and MCF-FP cells demonstrated decreased chemosensitivity compared to parental controls. Finally, the correlation between FP receptor and Slug was also confirmed immunohistochemically in breast cancer cases. Overall these results indicated that the actions of AKR1C3 can produce FP receptor ligands whose activation results in carcinoma cell survival in breast cancer. Highlights: FP receptor/AKR1C3 positive cases were associated with a trend towards worse outcome. 11β-PGF2α, a metabolite by AKR1C3, increased cell viability. 11β-PGF2α phosphorylated ERK and CREB and induced Slug via FP receptor. Correlation between AKR1C3/FP receptor and Slug was confirmed in breast tumors.